1985
DOI: 10.1007/bf02788638
|View full text |Cite
|
Sign up to set email alerts
|

The ac field patterns about living cells

Abstract: The presence of the small ac electric fields produced by living cells is shown by the gentle dielectrophoretic force on tiny dielectric particles. The beauty of the field patterns is made evident as the cell and particles settle in a hanging drop. Patterns characteristic of repulsion and of attraction, as well as of a dipolar and quadripolar nature, are observable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Pohl, published several papers about the interactions of live cells with dispersed particles [13][14][15][16][17]. The main purpose of these studies was to verify the hypothesis suggested in late 1960s by H. Frohlich who had proposed that live cells emit an AC electric field [18,19].…”
Section: Long-range Interactions Of Microparticles With Live Cellsmentioning
confidence: 89%
See 3 more Smart Citations
“…Pohl, published several papers about the interactions of live cells with dispersed particles [13][14][15][16][17]. The main purpose of these studies was to verify the hypothesis suggested in late 1960s by H. Frohlich who had proposed that live cells emit an AC electric field [18,19].…”
Section: Long-range Interactions Of Microparticles With Live Cellsmentioning
confidence: 89%
“…Later, he and his group realized that all charges are screened in aqueous electrolyte solutions. The screening would make it practically impossible to generate a low-frequency electric field by moving charges inside the cell (see discussion on page 54 in [17]). In the later review [16], Pohl mentioned that frequencies were on a MHz scale.…”
Section: Micro-dielectrophoresismentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic fields have the ability to extend over macroscopic distances, but lack the selective potential of the beacons of Banerjee et al (3). There is a growing awareness of the role of electromagnetic waves in living matter, how these affect cell function and are expressed in vivo (13,14), but mostly in the context of signaling rather than as a motive force.…”
mentioning
confidence: 99%